Wide-field multiplexed imaging of EGFR-targeted cancers using topical application of NIR SERS nanoprobes. (January 2015) - Mallia, Rupananda J; McVeigh, Patrick Z; Fisher, Carl J; Veilleux, Israel; Wilson, Brian C
Aim: As the possibilities of molecular imaging in personalized medicine evolve rapidly, the optical advantages of extremely narrow and intense spectral bands makes surface-enhanced Raman scattering (SERS) an appealing candidate for multiplexed recognition of targeted biomarkers over other optical imaging modalities.Materials & methods: In this proof-of-concept study, we report wide-field Raman detection of lung cancer using multimodal SERS nanoprobes specific to the EGF receptor family, both in vitro and in vivo .Results: For the first time, we demonstrate wide-field multiplexed Raman imaging for cancer detection in vivo after topical application of a 'cocktail' of SERS nanoprobes.Conclusion: This advancement represents a key step towards sensitive wide-field Raman endoscopic imaging of multiple biomarkers for early and accurate diagnosis of EGF receptor-expressing tumors of different internal organs.